2015
DOI: 10.1097/mca.0000000000000186
|View full text |Cite
|
Sign up to set email alerts
|

Significance of eosinophil accumulation in the thrombus and decrease in peripheral blood in patients with acute coronary syndrome

Abstract: Background and aimsIt is well known that the interaction between platelets (PLTs), endothelial cells, and leukocytes contributes to thrombosis in patients with acute coronary syndrome. The aim of this study was to investigate the significance of PLTs and eosinophils (EOS) in coronary arterial thrombi.MethodsPLT count, mean PLT volume, PLT mass, EOS count, EOS percentage, and troponin I level in peripheral blood were determined in 81 patients with angina pectoris (AP) and 49 patients with acute myocardial infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…Two retrospective studies and three cross sectional studies showed that there was a significant correlation between eosinophil count and the risk of CHD, but other studies found no association. 30,[38][39][40][43][44][45][46] Our retrospective study and meta-analysis found that eosinophil count had the significant association with the risk of CHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two retrospective studies and three cross sectional studies showed that there was a significant correlation between eosinophil count and the risk of CHD, but other studies found no association. 30,[38][39][40][43][44][45][46] Our retrospective study and meta-analysis found that eosinophil count had the significant association with the risk of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Of 16 studies, five studies were compatible for metaanalysis with a total of 889 CHD patients and 4306 controls (Table 3). 22,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Mean (±SD) We found that elevated leukocyte had a significant association with the incidence of CHD (OR 95%CI=3.57 [1.84-6.93], p<0.001) ( Table 3, Figure 2 A).…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study reported that eosinophil and basophil are prognostic factors for AMI. Jiang et al (20) found that eosinophil percentage was inversely correlated with cardiac troponin I level in AMI. Although that study suggested that eosinophil percentage was a potential prognostic factor, the prognostic value of eosinophil percentage was not further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Angina pectoris tends to be accompanied by thrombosis [18]. Therefore, drinking an adequate amount of water may help reduce blood coagulation and result in a lower OR for angina pectoris.…”
Section: Discussionmentioning
confidence: 99%